DIGITAL POLITICAL REPRESENTATION IN LOCAL ELECTIONS: SOCIAL MEDIA’S ROLE IN BANGKA BELITUNG - Zanuar Barep Prasetyo (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
The rise of social media has transformed political communication by enabling direct interaction between political actors and the public, including in local elections. This study examines strategies for strengthening political representation through social media and identifies factors affecting its effectiveness in building support bases in Bangka Belitung Province. Using a qualitative case study approach, data were collected through in-depth interviews, observations of campaign activities, and analysis of candidates’ social media content. The findings show that social media is used to build contextual political representation through narratives on local issues, candidate image-building based on achievements and personal closeness, and targeted communication strategies for different voter groups. Its effectiveness depends on factors such as campaign team capacity, public digital literacy, responsiveness to public opinion, data-driven evaluation, and integration with offline interactions. Overall, social media serves as a strategic tool in local political communication, but its success requires an integrated and context-sensitive approach. This study contributes to digital political communication research by providing local-level evidence and practical insights for developing adaptive campaign strategies in the social media era.